PENDIDIKAN KESEHATAN DENGAN MEDIA AUDIOVISUAL MENINGKATKAN PERILAKU IBU DALAM PENANGANAN INFEKSI SALURAN PERNAFASAN AKUT PADA BALITA DI KELURAHAN LEBIJAGA KABUPATEN NGADA - Kristina Blandina Wea; Kristiawati Kristiawati; Laily Hidayati (Critical Medical and Surgical Nursing Journal (CMSNJ), 2019)
Introduction: Acute Respiratory Infection (ARI) or respiratory infection is a major cause of morbidity and mortality in toddlers. ARI is a disease that often occurs both in adults and in children. Health education on the treatment of ARI in toddlers is very important to improve the knowledge, attitude, and skill of mothers in handling toddlers with ARI. The aimed of this study was to determine the effect of health education with audio-visual media on knowledge, attitude, and skill of mothers in the treatment of ARI in children under five years in Lebijaga Ngada.Methods: A quasi-experimental design was used in this study. The sample was 26 mothers of infants and toddlers who have a history of respiratory infection. The number of respondents was divided into 13 as the control group and 13 as the treatment group. Sampling was done by purposive sampling. The independent variable was health education using audiovisual media and the dependent variable was knowledge, attitude, and skill. Data were obtained through a questionnaire and analyzed using the Wilcoxon Signed Rank test and Mann Whitney U test with a significance level of α<0.05.Results: Health Education managed to increase knowledge with the results of Wilcoxon test p=0.001 The results of Mann Whitney p=0.000. It was similar happened to the attitude of the mother. The value Wilcoxon Signed Ranks Test for skill show significant value p=0.007 and Mann Whitney test results obtained significant value p = 0.000 which means effect obtained after the intervention. Conclusion: The results of can be concluded, there were effects of audiovisual on knowledge, attitude, and skill of mothers in the treatment of ARI in children under five years in Lebijaga Ngada Regency. Therefore, audiovisual media can be used by nurses as a good extension media in integrated service post.